2022
DOI: 10.1186/s12958-022-00983-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages phenotypes in the activation of resolution pathways within human granulosa cells

Abstract: Background Inflammatory state within the ovaries can disrupt normal follicular dynamics, leading to reduced oocyte quality and infertility. How the production of inflammatory mediators generated by macrophages with different gene expression profile (M1 and M2) might activate inflammatory pathways, such as cyclooxygenase-2 (COX-2) and 5-, 12-, and 15-lipoxygenase (LOX), in human granulosa cells (hGCs) remains unclear. Methods In this study, we evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…When exposed to different environments, macrophages are classified into classically activated macrophages (M1) with inflammatory and phagocytic properties and alternatively activated (M2) macrophages with anti-inflammatory and tissue remodeling and repair activities [ 83 ]. It has been reported that the proinflammatory environment related to M1 macrophages could influence the cell viability of human granulosa cells [ 84 ]. Moreover, macrophages are only found in the granulosa cell layer at advanced stages of atresia [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…When exposed to different environments, macrophages are classified into classically activated macrophages (M1) with inflammatory and phagocytic properties and alternatively activated (M2) macrophages with anti-inflammatory and tissue remodeling and repair activities [ 83 ]. It has been reported that the proinflammatory environment related to M1 macrophages could influence the cell viability of human granulosa cells [ 84 ]. Moreover, macrophages are only found in the granulosa cell layer at advanced stages of atresia [ 85 ].…”
Section: Discussionmentioning
confidence: 99%